Sublethal Photothermal Stimulation with a Micropulse Laser Induces Heat Shock Protein Expression in ARPE-19 Cells - Keiji Inagaki; Takuya Shuo; Kanae Katakura; Nobuyuki Ebihara; Akira Murakami; Kishiko Ohkoshi (Journal of Ophthalmology)
Purpose/Aim of the Study. Subthreshold micropulse diode laser photocoagulation is an effective treatment for macular edema. The molecular mechanisms underlying treatment success are poorly understood. Therefore, we investigated the effects of sublethal laser energy doses on a single layer of densely cultured ARPE-19 cells as a model of the human retinal pigment epithelium (RPE). Materials and Methods. A single layer of densely cultured human ARPE-19 cells was perpendicularly irradiated with a micropulse diode laser. Nonirradiated cells served as controls. Sublethal laser energy was applied to form a photocoagulation-like area in the cultured cell layers. Hsp70 expression was evaluated using quantitative polymerase chain reaction and immunocytochemistry. Results. Photocoagulation-like areas were successfully created in cultured ARPE-19 cell layers using sublethal laser energy with our laser irradiation system. Hsp70 mRNA expression in cell layers was induced within 30 min of laser irradiation, peaking at 3 h after irradiation. This increase was dependent on the number of laser pulses. Hsp70 upregulation was not observed in untreated cell layers. Immunostaining indicated that Hsp70 expression occurred concentrically around laser irradiation sites and persisted for 24 h following irradiation. Conclusion. Sublethal photothermal stimulation with a micropulse laser may facilitate Hsp70 expression in the RPE without inducing cellular damage.